A booklet containing 15 caricatures of Stalin as head of state of 15 diferent European countries and a portrait of Queen Wilhelmina, titled "Open carefuly, 16 heads of state in the Europe of the future." (1944)
A booklet containing 15 caricatures of Stalin as head of state of 15 diferent European countries and a portrait of Queen Wilhelmina, titled "Open carefuly, 16 heads of state in the Europe of the future."